Grundtvigianere, missionsfolk og genrejste apostle: Danske katolsk-apostolskes folkekirkelige baggrund og salmebøger - Christiansen, Benjamin Brandt (Kirkehistoriske Samlinger, 2021)
Fra 1850’erne til 1901 missionerede de katolsk-apostolske, kaldet irvingianerne, i Danmark og opbyggede menigheder i hele landet. Alligevel er de påfaldende underbelyste i dansk kirkehistorie. I denne artikel fremdrages Katolsk-apostolsk Kirke som et trossamfund, der evangeliserede i grundtvigske og indremissionske miljøer ud fra en overkonfessionel selvforståelse. Forbindelserne mellem Katolsk-apostolsk Kirke og folkekirkelige vækkelser belyses konkret gennem to betydningsfulde katolsk- apostolske gejstlige, Adolph Fleischer og Frederik Bertelsen. Fleischer havde grundtvigsk baggrund, imens Bertelsen på samme tid var katolsk-apostolsk og aktiv i Indre Mission. Endelig undersøges forbindelsernes mulige aftryk i katolskapostolske salmebøger. Summary In this article, I argue that the Catholic Apostolic Church took a particular interest in mission towards members of the revival movements within the Danish National Church, the Grundtvigians and the Inner Mission. Secondly, I argue that this tactic worked well and played a role in making Denmark perhaps the most successful mission per capita for the Catholic Apostolic Church. The eschatological and ecumenical message of the Catholic Apostolics found an audience within the Danish revival movements. Some of the highest serving clergymen of the Catholic Apostolic Church had their backgrounds in distinct movements such as the Grundtvigian and the Inner Mission. One of them, Frederik Bertelsen, even maintained his work within the Inner Mission simultaneously. Finally, I argue that these members brought a strong hymnal tradition with them into their new congregations. This resulted in a particularly Danish singing culture as well as an inclusion of a significant number of hymns by N.F.S. Grundtvig in Danish Catholic Apostolic hymnbooks. My analysis of these books shows that the Catholic Apostolics not only translated and wrote hymns, but also rewrote the hymns by Grundtvig in order to emphasise the imminent return of Christ.